Development of Destination Branding with Unique Selling Proposition Approach: A Case Study at Kampung Adat Ratenggaro, NTT - Caesar Achmad Firjaun Faqih Aziz; Yumna Alifa; Pringgo Dwiyantoro; Banung Grahita (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2025)
This study explores on the development of destination branding for Kampung Adat Ratenggaro, a traditional village in East Nusa Tenggara, Indonesia, using the Unique Selling Proposition (USP) approach. The research aims to identify and leverage the village's cultural and natural assets to create a compelling brand identity. The scope includes an analysis of current tourism conditions, strategic opportunities, and the formulation of branding strategies tailored to highlight destination uniqueness. A qualitative approach was employed, incorporating SOAR analysis using Internal & External Factor Analysis Summary to prioritize strategic initiatives and mapping strengths, weaknesses, opportunities, and aspirations. Key findings reveal that Kampung Adat Ratenggaro holds significant potential as a cultural tourism destination, supported by its architectural heritage, traditional weaving, and vibrant ceremonies. The proposed branding concept, "Harmony of Tana Uma Tau," emphasizes the harmonious relationship between nature, culture, and people. This approach strengthens market positioning, enhances competitiveness, and promotes sustainable tourism development. The study concludes that a USP-driven branding strategy, combined with stakeholder collaboration, can effectively increase tourism appeal and community engagement. Recommendations include the implementation of digital marketing campaigns, infrastructure development to improve visitor experience, and capacity-building programs for local stakeholders. These efforts aim to establish Kampung Adat Ratenggaro as a leading cultural tourism destination, contributing to Indonesia's broader cultural tourism agenda.